2020
DOI: 10.21037/tau-19-687
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of nomograms for the prediction of postoperative survival of patients with grade 4 renal cell carcinoma (RCC)

Abstract: Background: To develop successful prognostic models for grade 4 renal cell carcinoma (RCC) following partial nephrectomy and radical nephrectomy. Methods:The nomograms were established based on a retrospective study of 135 patients who underwent partial and radical nephrectomy for grade 4 RCC at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In our study, T stage, M stage, and pathological grade were independent predictors of LNM, Patients with high-level pathological grade, and advanced T and M stages had a higher risk of LNM, probably indicating that tumors were closely related to much more drastic aggressive, which was similar to previous studies (17,18,(36)(37)(38). Meanwhile, Figure 5 also showed that the T stage and M stage were the top two important variables in our five models.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, T stage, M stage, and pathological grade were independent predictors of LNM, Patients with high-level pathological grade, and advanced T and M stages had a higher risk of LNM, probably indicating that tumors were closely related to much more drastic aggressive, which was similar to previous studies (17,18,(36)(37)(38). Meanwhile, Figure 5 also showed that the T stage and M stage were the top two important variables in our five models.…”
Section: Discussionsupporting
confidence: 88%
“…[21]However, TNM staging contains only tumor size, lymph node metastatic status, as well as information on distant metastases. [22], [23], [24]Therefore, we designed a nomogram combining more information to predict the survival prognosis of young renal cancer patients. In our study, our nomogram shows greater accuracy and clinical utility than TNM staging based on the results of ROC curves, C index, and DCA curves, which demonstrates the strength of our nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Survival prediction is an ongoing challenge in RCC. Multiple different models have been developed already, but none of them has incorporated AI-based image analysis [29][30][31]. Thus, in our study, we trained a CNN to predict 5y-OS.…”
Section: Discussionmentioning
confidence: 99%